2008
DOI: 10.1097/01.ncq.0000324587.53719.2f
|View full text |Cite
|
Sign up to set email alerts
|

Restraint Management

Abstract: Restraint management continues to be a challenge despite years of attention to the issue. This article demonstrates how a restraint prevention program, built on an analysis of care processes and a set of "bundled" interventions, can successfully decrease restraint prevalence and enhance safe patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…There is also evidence that patients with psychiatric illness such as bipolar disorder,40 dementia, or depression are at greater risk for delirium 41. The use of physical or chemical restraints in the treatment of delirium has been studied in other settings such as skilled nursing facilities42 and intensive care units,43 and restraint prevention programs have been suggested 44. Several studies have shown that most patients will be cooperative with an oral dosing regimen despite the belief that they may be too agitated or uncooperative 45.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that patients with psychiatric illness such as bipolar disorder,40 dementia, or depression are at greater risk for delirium 41. The use of physical or chemical restraints in the treatment of delirium has been studied in other settings such as skilled nursing facilities42 and intensive care units,43 and restraint prevention programs have been suggested 44. Several studies have shown that most patients will be cooperative with an oral dosing regimen despite the belief that they may be too agitated or uncooperative 45.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies used a controlled study design: two studies were randomised controlled trials (one used a parallel-group design (Kwok et al, 2006) and one a stepped-wedge design (Enns et al, 2014)), two studies were nonrandomised controlled clinical trials (Lai et al, 2011(Lai et al, , 2013, and one study used a nonrandomised crossover design (Lever et al, 1995). We also found 11 pre-post studies (Amato et al, 2006;Antonelli, 2008;Beaulieu et al, 2008;Eskandari et al, 2018;Hanger et al, 1999;Hevener et al, 2016;Johnson et al, 2016;Köbke & Brase, 2017;Lin et al, 2018;Mion et al, 2001;Özdemir & Karabulut, 2009;Powell et al, 1989;Smith et al, 2003). All quality improvement projects used pre-post designs for evaluation, but the majority of publications did not provide detailed information about the study design.…”
Section: Characteristics Of Included Studies and Quality Improvemenmentioning
confidence: 76%
“…Sixteen publications reported on intervention studies (Amato, Salter, & Mion, 2006;Antonelli, 2008;Beaulieu et al, 2008;Enns, Rhemtulla, Ewa, Fruetel, & Holroyd-Leduc, 2014;Eskandari, Abdullah, Zainal, & Wong, 2018;Hanger, Ball, & Wood, 1999;Hevener, Rickabaugh, & Marsh, 2016;Johnson et al, 2016;Kwok, Mok, Chien, & Tam, 2006;Lai, Chow, Suen, & Wong, 2011Lever, Molloy, Bedard, & Eagle, 1995;Lin, Liao, Yu, Chu, & Ho, 2018;Özdemir & Karabulut, 2009;Powell, Mitchell-Pedersen, Fingerote, & Edmund, 1989;Smith, Timms, Parker, Reimels, & Hamlin, 2003) and 15 publications on projects (Cosper, Morelock, & Provine, 2015;Hall et al, 2018;Hancock et al, 2001;Jensen et al, 1998;Johnson & Beneda, 1999;Kirk, McGlinsey, Beckett, Rudd, & Arbour, 2015;Köbke & Brase, 2017;Markwell, 2005;Mion et al, 2001;Missildine & Harvey, 2000;Mitchell, Panchisin, & Seckel, 2018;Morrison et al, 2000;Rieth & Bennett, 1998;Swauger & Tomlin, 2000;Zoellner-Hunter, Goetz, & Czurylo, 2000) (see Tables 1 and 2). Articles were published between 1989 and 2018.…”
Section: Characteristics Of Included Studies and Quality Improvemenmentioning
confidence: 99%
See 2 more Smart Citations